2017
DOI: 10.1016/j.bpj.2017.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Human Erythrocyte Skeleton-Bilayer Dissociation during Splenic Flow

Abstract: Prospects of vesiculation occurring during splenic flow of erythrocytes are addressed via model simulations of RBC flow through the venous slits of the human spleen. Our model is multiscale and contains a thermally activated rate-dependent description of the entropic elasticity of the RBC spectrin cytoskeleton, including domain unfolding/refolding. Our model also includes detail of the skeleton attachment to the fluidlike lipid bilayer membrane, including a specific accounting for the expansion/contraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 59 publications
5
46
1
Order By: Relevance
“…The molecular mechanism underlying vesiculation in the spleen is unknown, but may involve a combination of biochemical and biophysical stress. Recent model simulations support the involvement of degraded hemoglobin in reducing the cytoskeleton/membrane connection, thereby promoting microvesicle shedding during splenic flow ( Zhu et al, 2017 ). Thus, the mechanical and biochemical circumstances in the spleen, together with the presence of specialized macrophages, may make the spleen a microvesicle-based quality control and repair system.…”
Section: The Role Of the Spleenmentioning
confidence: 90%
“…The molecular mechanism underlying vesiculation in the spleen is unknown, but may involve a combination of biochemical and biophysical stress. Recent model simulations support the involvement of degraded hemoglobin in reducing the cytoskeleton/membrane connection, thereby promoting microvesicle shedding during splenic flow ( Zhu et al, 2017 ). Thus, the mechanical and biochemical circumstances in the spleen, together with the presence of specialized macrophages, may make the spleen a microvesicle-based quality control and repair system.…”
Section: The Role Of the Spleenmentioning
confidence: 90%
“…Accumulation of Band3 and actin, which contrasts with the absence of spectrin in MVs generated upon RBC aging and blood storage, supports the hypothesis that partial membrane:cytoskeleton uncoupling, due to the breakage of ankyrin:Band3 binding, could contribute to the vesiculation process [ 21 ]. Accordingly, a simulation study highlighted that a significant reduction of the local anchorage density is required for vesiculation [ 119 ]. Furthermore, it has been shown that cytoskeleton stiffness and density both increase upon RBC senescence, leading to larger compressive forces on the cell membrane.…”
Section: Microvesicle Biogenesis and Shedding—general Mechanismsmentioning
confidence: 99%
“…The function of spleen in sensing and clearing RBCs with alterations in their size, shape, and deformability has been elucidated through in vivo ( 13 , 14 ), ex vivo ( 3 5 ), and in vitro ( 15 17 ) experiments and computational modeling ( 18 21 ). However, the role of IES in filtering RBCs with significant membrane protein defects, as seen in HS and HE, has not been investigated in sufficient detail.…”
mentioning
confidence: 99%